Limit state numerical procedures for cyclically loaded elastoplastic structures - Παναγιώτου, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2015)
Development of novel numerical procedures for a) the prediction of limit states of cyclically loaded elastoplastic structures and b) for the shakedown analysis of structures